Architecture's Historical Turn : Phenomenology and the Rise of the Postmodern - Otero-Pailos, Jorge (Book collections on Project MUSE., 2010)
This text traces the hidden history of architectural phenomenology, a movement that reflected a key turning point in the early phases of postmodernism and a legitimating source for those architects who first dared to confront history as an intellectual problem and not merely as a stylistic question.